PENGEMBANGAN BAHAN AJAR BERBASIS CERITA BERGAMBAR UNTUK MENINGKAT PEMAHAMAN BELAJAR BAHASA INDONESIA PADA KELAS II DI SD NEGERI 95 PALEMBANG - Yuyun Desti; Liza Murniviyanti; Aldora Pratama (Indonesian Journal of Elementary Education (IJETE), 2025)
The development of illustrated story-based teaching materials to improve understanding of learning Indonesian in class II, has the goal of knowing the development of understanding of learning Indonesian that is valid, practical and effective. The type of research used by researchers in developing teaching materials based on picture stories is research and development, development refers to the ADDIE model consisting of analysis design, development, implementation, and evaluation. The research subjects were class IIA and IIB students of Public Elementary School 95 Palembang with a total of 36 students. The data collection techniques used in the study were questionnaires and documentation, based on the results of expert validator research from the three fields, namely media, material, and language where the validator in In this development, there are 2 validators covering the three fields, so the validator percentage results from the two experts are 3.80 which are categorized as "valid". Then the teacher's response practicality test obtained a percentage result of 87.49%, categorized as "very practical", then the one to one trial obtained a percentage value of 87.49% categorized as very practical, then the small group trial obtained a percentage value of 79.27 %. And the last test of the potential effect test obtained a percentage value of 90.00% which was categorized as very effective.